O contestado : movimento social e seu desdobramento na atual situação da região - Rosa, Geraldo Antônio da (2007)
The present work aims to reflect on the "Contestado": social movement and its extending in the current educational situation of the region. This research integrates the Area of Concentration: religion and education, focusing on perspectives theological and educational. The "Contestado", is characterized as a social movement of great magnitude, being relegated historically to second plan, as the majority of the social movements. The thesis focus on the results of beforehand, for the education, of the known events as the "Contestado" war. From the current situation of the region it will be searched in the past, elements for the analysis of the conditions and the involved mechanisms in the related social-historical process. The first chapter analyzes the conceptual categories: social movement, messianism, Weber s sociological concept of charismatic authority, peasant, liberating education and liberation theology. The second chapter presents a historical panorama of the "Contestado", following the specified project of analysis: The Land - scene of innumerable episodes; the Contestado's man and social structure and the "Contestado" war. In the third chapter refers towards the analysis of the disappearance of the allusive plate to the movement of "Contestado" and the instituted educational process in the region. The last chapter presents the conceptualization of the curriculum and the influence of the means of production in the school s curriculum of the basic education. In addiction, it will also be analyzed the importance that is being given to the Regional History and the "Contestado" in the pertaining to school s curriculum of the basic education, analyzing pupils egresses of high school and history s teachers of the Public System of the State of Santa Catarina.